Before solving, let's determine the restrictions on the variable. A radical is undefined it the number inside is less than 0.
We must therefore set up an inequality and solve:
#sqrt(x + 4) >= 0#
#sqrt(2x - 1) >= 0#
and
#3sqrt(x - 1) >= 0#
Solving each we get that
#x >= -4#
#x >= 1/2#
and
#x >= 1#
We must pick the largest of these, since if we pick one of the smaller ones the equation will become undefined. The largest is #x >=1#; this is our restriction statement. To justify the point I made earlier in this paragraph, try substituting a number smaller than #1# into the equation. For example, #x= -2#
#sqrt(-2 + 4) + sqrt(2 xx -2 - 1) = 3sqrt(-2 - 1)#
#sqrt(2) + sqrt(-5) = 3sqrt(-3)#
In this case, two radicals are undefined. Now that we have defined any restrictions on the variable, we can proceed with solving. This can be started by squaring both sides
#(sqrt(x + 4) + sqrt(2x - 1))^2 = (3sqrt(x - 1))^2#
#x + 4 + 2sqrt(x + 4)sqrt(2x - 1) + 2x - 1 = 9(x - 1)#
#3x + 3 + 2sqrt(x + 4)sqrt(2x - 1) = 9x - 9#
# 2sqrt(x + 4)sqrt(2x - 1) = 6x - 12#
#sqrt(x + 4)(sqrt(2x - 1)) =( cancel(2)(3x - 6))/cancel(2)#
Since the radicals are both square roots, we can combine them in multiplication.
#sqrt((x + 4)(2x - 1)) = 3x - 6#
#sqrt(2x^2 + 8x - x - 4) = 3x - 6#
#(sqrt(2x^2 + 7x - 4))^2 = (3x - 6)^2#
#2x^2 + 7x - 4 = 9x^2 - 36x + 36#
#0 = 7x^2 - 43x + 40#
#0 = 7x^2 - 8x - 35x + 40#
#0 = 7x(x - 8/7) - 35(x - 8/7)#
#0 = (7x - 35)(x - 8/7)#
#x = 5 and 8/7#
Checking both answers in the original equation, we find that only #x = 5# works.
Therefore, our solution set is #{x = 5, x >= 1}#
Hopefully this helps!